2004
DOI: 10.1136/jech.58.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Traffic related air pollution and incidence of childhood asthma: results of the Vesta case-control study

Abstract: Study objective: The Vesta project aims to assess the role of traffic related air pollution in the occurrence of childhood asthma. Design and setting: Case-control study conducted in five French metropolitan areas between 1998 and 2000. A set of 217 pairs of matched 4 to 14 years old cases and controls were investigated. An index of lifelong exposure to traffic exhausts was constructed, using retrospective information on traffic density close to all home and school addresses since birth; this index was also ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
116
0
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(134 citation statements)
references
References 35 publications
(26 reference statements)
6
116
0
8
Order By: Relevance
“…In France, a study of lifetime traffic exposure in young children found that exposure in the first 3 years of life was significantly associated with a diagnosis of asthma after controlling for known risk factors (Zmirou et al, 2004). In Belfast, Ireland, admissions to the emergency room for asthma were related to air pollutants in a time series analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In France, a study of lifetime traffic exposure in young children found that exposure in the first 3 years of life was significantly associated with a diagnosis of asthma after controlling for known risk factors (Zmirou et al, 2004). In Belfast, Ireland, admissions to the emergency room for asthma were related to air pollutants in a time series analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Though many studies of the chronic health effects associated with long-term exposure to air pollution (often from large, well-known cohorts) examine the use of an alternative exposure metric in an epidemiologic study (Adar et al 2013;Brauer et al 2002;Jerrett et al 2008;Puett et al 2011;Young et al 2014;Zmirou et al 2004), only the seven studies found by the authors and described below examine multiple approaches to exposure assessment, and include comparison of the epidemiologic results obtained when using each exposure metric. However, many manuscripts lacked definitive conclusions about which exposure metric was most beneficial, and the wide range of health outcomes, exposure metrics, and exposure durations of interest used make it difficult to draw larger conclusions from these studies.…”
Section: Studies Of Chronic Health Effects Associated With Long-term mentioning
confidence: 99%
“…(Gordian et al, 2006;Zmirou et al, 2004;Brauer et al, 2002), 천식으로 인한 입원율을 높이고 (Lin et al, 2002;Edwards et al, 1994) 참 고 문 헌…”
unclassified